2021
DOI: 10.1186/s40662-021-00259-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of implanted perforated lacrimal punctal plugs using anterior segment optical coherence tomography

Abstract: Purpose Evaluation of the patency and position of perforated lacrimal punctal plugs implanted for treating punctal stenosis together with quantitative assessment of the precorneal tear film using anterior segment optical coherence tomography (AS-OCT). Methods In a prospective study, the lower punctum of 54 eyes of 29 patients implanted with perforated punctal plugs were examined using AS-OCT during the early postoperative period. Preoperative tear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…In a study of Abdallah RMA et al, [ 15 ] they evaluated the patency and position of perforated lacrimal punctal plugs implanted for treating punctal stenosis together with quantitative assessment of the tear film using AS-OCT, they found that There was a statistically significant postoperative decrease of tear meniscus area and tear meniscus area ( P < 0.001) and postoperative epiphora Munk score ( P < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…In a study of Abdallah RMA et al, [ 15 ] they evaluated the patency and position of perforated lacrimal punctal plugs implanted for treating punctal stenosis together with quantitative assessment of the tear film using AS-OCT, they found that There was a statistically significant postoperative decrease of tear meniscus area and tear meniscus area ( P < 0.001) and postoperative epiphora Munk score ( P < 0.001).…”
Section: Discussionmentioning
confidence: 99%